Ovalbumin Messenger RNA: Evidence That the Initial Product of Transcription Is the Same Size as Polysomal Ovalbumin Messenger - McKnight, G. Stanley (1974)
The messenger RNA for ovalbumin, the major secretory protein of the chick oviduct, appears not to be made as a high-molecular-weight precursor when artifacts due to aggregation are eliminated. No ovalbumin messenger RNA sequences that will hybridize to complementary DNA made against ovalbumin mRNA are found in concentrated samples of hen oviduct RNA larger than 28 S. The sensitivity of the hybridization assay is sufficient to detect less than one molecule of ovalbumin mRNA precursor per tubular gland cell. Newly synthesized ovalbumin messenger RNA isolated from immature chicks stimulated briefly by estrogen is the same size as that found in hen polyribosomes. We conclude that ovalbumin messenger RNA does not undergo any significant change in molecular weight from its initial transcription to its incorporation into polyribosomes.